Thermally activated delayed fluorescent polymer- assisted morphological control on perfluorinated ionomer enriched surface and exciton harvesting for phosphorescent organic light-emitting devices. (December 2020) - Gao, Yuhan; Tang, Yang; Liu, Hengjia; Xie, Guohua; Yang, Chuluo
Abstract: Poly(3, 4-ethylenedioxythiophene):poly (styrenesulfonic acid) (PEDOT:PSS) is one of the most successful conductive polymers, usually used as hole injecting layer in organic light-emitting devices. Due to the enhanced conductivity and tunable work function (WF), the modification of PEDOT:PSS with some additives has been proved to be cost-effective. Perfluorinated ionomer (PFI) has been reported as an effective additive to improve the WF of PEDOT:PSS, increasing from 5.2 eV to 5.95 eV with a recipe of PEDOT(1):PSS(6):PFI(25). However, the strong hydrophobicity of PFI has limited the choice of the organic solvents used to fabricate the uniform emitting layer on the modified PEDOT:PSS. To address this issue, the polymers were introduced as the additives of the emitter to overcome the non-uniform morphology on the hydrophobic surface of PEDOT:PSS:PFI. A conventional fluorescent polymer poly(9-vinylcarbazole) (PVK) and a thermally activated delayed fluorescent polymer (4-(2-(9-(heptadecan-9-yl)-6-phenyl-9H-carbazol-3-yl)-9, 9-dihexyl-7-phenylacridin-10(9H)-yl)phenyl) (phenyl)methanone (PABPC2.5) were compared in parallel to reveal the influence of the polymer additive of the emitters on the overall performances of the devices. The control device based on the PFI-modified PEDOT:PSS achieved a maximum current efficiency (CE) of 0.14 cd A −1, without any polymer additives in the emitting layer. In contrast, the CE of the devices with PVK and PABPC2.5 were dramatically elevated to 7.1 cd A -1 and 4.5 cd A −1 respectively, when a small molecular thermally activated delayed fluorescence compound was employed as the emitter. Enabled by an easily soluble phosphorescent emitter acetylacetonatobis(4-(4- tert -butylphenyl)-thieno[3, 2-c]pyridinato-C2, N)iridium (PO-01-TB). The device with PABPC2.5 as the additive obtained a maximum CE of 42.0 cd A −1, which is significantly higher than 15.7 cd A −1 of the one with the additive PVK, attributed to the energy transfer in the emitting layer. The polymer additives not only overcome the issue of the hydrophobicity of the modified PEDOT:PSS but endow the exciton harvesting from the polymer to the small molecular emitters. Graphical abstract: Polymer additive demonstrated effective morphological control. Attributed to the synergetic energy transfer to the emitter, thermally activated delayed fluorescent polymer-based device obtained an improvement factors of 2.7 in current efficiency. Image 1 Highlights: Polymer additives in the emitting layer improved film forming property on the hydrophobic surface. TADF polymer additive sensitized the phosphorescent emitter. Synergetic energy transfer occurred from host and TADF polymer to emitter. The EQE of solution-processed PhOLED exhibited an improvement factor of 168% in the presence of a TADF additive.